'What happens when I can no longer care?' Informal carers' concerns about facing their own illness or death: a qualitative focus group study. Issue 8 (3rd September 2019) - Greenwood, Nan; Pound, Carole; Brearley, Sally
Abstract : Objectives: Older informal carers play an increasingly important role in supporting others with long-term health conditions. This study aimed to explore in depth the perspectives of older carers (70+ years) supporting others with a variety of conditions and disabilities focusing on their thoughts and experiences about when they are unable to continue caring. Design: Qualitative with four focus groups. Setting: Greater London, UK. Participants: 28 older carers (70+ years) recruited from the voluntary sector participated in this study. Most were women and many were spouses caring for partners with age-related conditions such as dementia, arthritis and visual impairment. Nearly a third were parents of adult children with severe physical or cognitive disabilities. Findings: Thematic analysis identified two main aspects for carers when contemplating the future—when they are unable to care in the short term or long term if they die or can no longer manage. Themes included the following: the impact of age, health conditions and relationships on future planning; anxiety about future care; carers' ambivalence and challenges in broaching the subject; interventions that might help older carers talk about and plan for the future of those they care for. Conclusions: Services need to be open to talking about this difficult topic. Our findings suggest that frank discussions about when older carers cannot care and having plans in place, whether these are financial or address other practical issues, makes it easier for all concerned. However, this issue is not easily broached and its timing and ways to access this support must be carefully and individually gauged. Future research with more diverse demographic groups is needed to improve understanding of these carers' perspectives. Research is also needed to develop interventions to support older carers to talk about and plan for the future.